2001
DOI: 10.1053/ejvs.2001.1448
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide: Implications for Vascular and Endovascular Surgery

Abstract: Nitric oxide has a key role in vascular homeostasis. It plays a protective role by suppressing abnormal proliferation of vascular smooth muscle following various pathological situations including atherosclerosis and restenosis after vascular interventions such as balloon angioplasty, stent deployment and bypass grafting. It also has strong antiplatelet and anti-thrombogenic properties. In this review, possible applications to daily vascular and endovascular surgery practice, including systemic use of NO donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 69 publications
0
33
1
Order By: Relevance
“…NO produced from eNOS is a key regulator of vascular homeostasis, including basal vascular tone (blood flow) and blood pressure (34), as well as acting as an anti-thrombogenic agent (32). An impairment of endothelium-dependent relaxation is present in atherosclerotic vessels even before vascular structural changes occur and represents the reduced eNOSderived NO activity (16).…”
Section: Discussionmentioning
confidence: 99%
“…NO produced from eNOS is a key regulator of vascular homeostasis, including basal vascular tone (blood flow) and blood pressure (34), as well as acting as an anti-thrombogenic agent (32). An impairment of endothelium-dependent relaxation is present in atherosclerotic vessels even before vascular structural changes occur and represents the reduced eNOSderived NO activity (16).…”
Section: Discussionmentioning
confidence: 99%
“…NO has several critical functions in the vascular system, maintaining vascular homeostasis and acting as a potent vasodilator, regulator of vascular cell proliferation and migration, and inhibitor of thrombus formation. [30][31][32][33][34][35][36] À functional group, are being investigated as NO-releasing pharmaceuticals [37][38][39][40][41] and thromboresistant coatings for blood-contacting medical devices. 40,[42][43][44][45][46][47][48][49] NOreleasing materials have been shown to inhibit platelet adhesion and aggregation, 40,[42][43][44][45][46][47][48][49][50][51][52][53] as well as decreasing the incidence of intimal hyperplasia in several animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate, nitrite and superoxide anions are released from SIN-1 during the liberation of NO. Systemic delivery of SIN-1 inhibits platelet adhesion and smooth muscle cell proliferation in following balloon-induced carotid injury in pigs. This compound also inhibited thrombus formation when given systemically (Vural and Bayazit, 2001). Furthermore, from the ACCORD study which involved the systemic administration of molsidomine and linsidomine to patients undergoing coronary angioplasty, suggested a modest immediate improvement in lumimal diameter (Lablanche et al, 1997).…”
Section: Heterocyclic No Donorsmentioning
confidence: 97%
“…maintenance of vascular tone and inhibition of platelet aggregation). Also, it has been shown that administration of RSNOs following balloon angioplasty attenuates intimal and medial proliferation implying a therapeutic role for them in the prevention of restenosis (see review Vural and Bayazit, 2001). Also, RSNOs have been shown to reduce platelet deposition and inhibit neointimal proliferation after vascular injury (Vural and Bayazit, 2001).…”
Section: S-nitrosothiolsmentioning
confidence: 99%